GITR modulates innate and adaptive mucosal immunity during the development of experimental colitis in mice. Issue 1 (8th June 2006) - Santucci, L; Agostini, M; Bruscoli, S; Mencarelli, A; Ronchetti, S; Ayroldi, E; Morelli, A; Baldoni, M; Riccardi, C
Abstract : Background: Uncontrolled T cell activation and abnormal function of the innate immune system against normal enteric bacterial flora play a critical part in the pathogenesis of inflammatory bowel disease (IBD). Therefore, pharmacological strategies directed to restore the normal responsiveness of the immune system could be efficacious in the treatment of these pathological conditions. Glucocorticoid-induced tumour necrosis factor receptor (GITR)-related gene is a member of the tumour necrosis factor receptor superfamily that is constitutively expressed at high levels on regulatory T cells and at low levels on unstimulated T cells, B cells and macrophages. GITR triggering leads to activation of T effectors and reversal of suppressive function of regulatory T cells. Aim: To investigate the role of GITR in the development of experimental colitis in mice. Results: Using GITR −/− mice, GITR deletion protected against 2, 4, 6-trinitrobenzene sulphonic acid (TNBS)-induced colitis by reducing innate immune responses and effector T cell activity. Effector T cells isolated from GITR −/− mice were less effective than T cells isolated from GITR +/+ mice to transfer colitis in immunodeficient mice. Blocking the GITR/ligand for GITR (GITRL) signal by giving soluble GITR prevented TNBS-induced colitis in normal GITR +/+ and also in lymphocyte-deficient SCID mice. Conclusions: Collectively, these data suggest that GITR plays a critical part in regulating both acquired and innate mucosal immune responses during the development of experimental colitis in mice. Therefore, targeting the GITR/GITRL system signalling may represent a potential pharmacological tool for the treatment of IBD.